UMPSA and Liuzhou Railway Vocational Technical College (LRVTC) collaboration empowers Advanced TVET - Azrizulazmi, Bustan; Mimi Rabita, Abd Wahit (UMPSA, 2024)
GUANGXI, CHINA, 24 June 2024 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) is leading the way in the implementation of student mobility programmes that have major implications in improving students’ global skills while enriching learning with overseas experiences.